Extended criterion for absence of fixed points - Kazymyrov, O. (ХНУРЭ, 2013)
One of the criteria for selecting substitutions used in block ciphers is the absence of fixed points. This paper shows that this criterion must be extended taking into consideration mixing key function. It is shown that modulo addition has more advantages than XOR operation. It is shown in practice that encryption procedure of AES has a natural isomorphic form when fixed points are reached.
Keywords: fixed points; АЕS; criterion; s-box